Culture and Identity of People Living in the Indo-Bangla Borderlands - Atiquzzaman, Sharif (Literary Studies, 2025)
Borderlands are regions situated near the lines separating two countries or areas. Nations secure their boundaries by controlling the entry and exit of foreign citizens and protecting their people from dangers or threats posed by cross-border movements. In the Indo-Bangla Borderlands, numerous fragile and contested issues have arisen since the colonial demarcation in 1947. Each state frames its foreign policies with the intent of controlling its porous boundaries, though local realities often differ. The porosity of these borderlands, arbitrarily drawn at some points, has encouraged infiltrations, primarily for illegal trades. This desperate act for survival has turned the borderlands into smugglers’ paradises, but it also opens up possibilities for wider demographic and potentially dangerous political changes. As structural entities, borders can generate diverse effects by facilitating crossings that can either integrate or segregate people. Borderlands are also emotional spaces, connected to people through memory and identity (Ranjan 28). They are often termed ‘peripheral’ and ‘marginalised’ due to their isolation from the mainland. For the inhabitants of these regions, the concept of a ‘border’ carries no political implication. Instead, survival is their primary concern. They coexist with their geographical environments to meet their basic needs such as food, clothing, and medical treatment. The modern concept of the border holds little meaning for the mass-dwellers in the borderlands. In many cases, the political and cultural boundaries of a country do not align with cultural fluidity, leading to reunification. The people living in these border areas exhibit unique cultural prototypes in their lifestyle. This study will focus on how the culture and identity of borderland inhabitants have been affected by the borders.